RNA-Sequencing Analysis Revealed a Distinct Motor Cortex Transcriptome in Spontaneously Recovered Mice After Stroke. Issue 9 (September 2018) - Ito, Masaki; Aswendt, Markus; Lee, Alex G.; Ishizaka, Shunsuke; Cao, Zhijuan; Wang, Eric H.; Levy, Sabrina L.; Smerin, Daniel L.; McNab, Jennifer A.; Zeineh, Michael; Leuze, Christoph; Goubran, Maged; et al.
Abstract : Background and Purpose—: Many restorative therapies have been used to study brain repair after stroke. These therapeutic-induced changes have revealed important insights on brain repair and recovery mechanisms; however, the intrinsic changes that occur in spontaneously recovery after stroke is less clear. The goal of this study is to elucidate the intrinsic changes in spontaneous recovery after stroke, by directly investigating the transcriptome of primary motor cortex in mice that naturally recovered after stroke. Methods—: Male C57BL/6J mice were subjected to transient middle cerebral artery occlusion. Functional recovery was evaluated using the horizontal rotating beam test. A novel in-depth lesion mapping analysis was used to evaluate infarct size and locations. Ipsilesional and contralesional primary motor cortices (iM1 and cM1) were processed for RNA-sequencing transcriptome analysis. Results—: Cluster analysis of the stroke mice behavior performance revealed 2 distinct recovery groups: a spontaneously recovered and a nonrecovered group. Both groups showed similar lesion profile, despite their differential recovery outcome. RNA-sequencing transcriptome analysis revealed distinct biological pathways in the spontaneously recovered stroke mice, in both iM1 and cM1. Correlation analysis revealed that 38 genes in the iM1 were significantly correlated with improved recovery, whereas 74 genes were correlated in the cM1. In particular, ingenuity pathway analysis highlighted the involvement of cAMP signaling in the cM1, with selective reduction of Adora2a (adenosine receptor A2A), Drd2 (dopamine receptor D2), and Pde10a (phosphodiesterase 10A) expression in recovered mice. Interestingly, the expressions of these genes in cM1 were negatively correlated with behavioral recovery. Conclusions—: Our RNA-sequencing data revealed a panel of recovery-related genes in the motor cortex of spontaneously recovered stroke mice and highlighted the involvement of contralesional cortex in spontaneous recovery, particularly Adora2a, Drd2, and Pde10a-mediated cAMP signaling pathway. Developing drugs targeting these candidates after stroke may provide beneficial recovery outcome. Abstract : Supplemental Digital Content is available in the text.